Cathode material, its manufacturing method and lithium secondary battery including same

A bimodal particle size distribution and coating for lithium composite transition metal oxides in positive electrodes address cracking issues, enhancing stability and life in lithium secondary batteries.

JP7670424B2Active Publication Date: 2025-04-30LG CHEM LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023560902
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-08-25
Filing Date
2022-08-17
Publication Date
2025-04-30
Estimated Expiration
2042-08-17

Smart Images

  • Figure 0007670424000004
    Figure 0007670424000004
  • Figure 0007670424000005
    Figure 0007670424000005
  • Figure 0007670424000006
    Figure 0007670424000006
Patent Text Reader

Abstract

The present invention relates to a cathode material, and 50 A positive electrode material having a bimodal particle size distribution including a first positive electrode active material and a second positive electrode active material having different average particle diameters (D ) from each other, the first positive electrode active material including a lithium composite transition metal oxide, and the average particle diameter (D ) at which the maximum peak of the area-accumulated particle size distribution of the first positive electrode active material is shown as measured by a laser diffraction particle size measurement device. 50 The present invention relates to a cathode material having a secondary particle having a number of primary particles of 6 to 30 as measured by a cross-sectional SEM image of the secondary particle, a method for producing the cathode material, and a lithium secondary battery including the cathode material.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2021-0112328 filed on August 25, 2021, and all contents disclosed in the documents of said Korean patent application are incorporated by reference into this specification.

[0002] The present invention relates to a method for determining the average particle size (D 50 The present invention relates to a positive electrode material having a bimodal particle size distribution including positive electrode active materials having mutually different particle sizes, a method for producing the same, and a lithium secondary battery including the same. [Background technology]

[0003] Recently, with the rapid spread of electronic devices using batteries, such as mobile phones, notebook computers, and electric vehicles, the demand for secondary batteries that are small, lightweight, and have a relatively high capacity is rapidly increasing. In particular, lithium secondary batteries are lightweight and have high energy density, and are in the spotlight as a driving power source for portable devices. Accordingly, research and development efforts are being actively made to improve the performance of lithium secondary batteries.

[0004] In a lithium secondary battery, an organic electrolyte or a polymer electrolyte is filled between a positive electrode and a negative electrode, which are made of active materials that allow the intercalation and deintercalation of lithium ions, and electrical energy is generated by oxidation and reduction reactions that occur when lithium ions are inserted and extracted at the positive and negative electrodes.

[0005] Lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMnO2 or LiMn2O4, etc.), lithium iron phosphate compound (LiFePO4), etc. have been used as positive electrode active materials for lithium secondary batteries. Among them, lithium cobalt oxide (LiCoO2) is widely used due to its advantages of high operating voltage and excellent capacity characteristics, and is applied as a positive electrode active material for high voltage. However, due to the rising price of cobalt (Co) and unstable supply, there are limitations to its mass use as a power source in fields such as electric vehicles, and there is an increasing need to develop a positive electrode active material that can be used instead.

[0006] For this reason, nickel-cobalt-manganese-based lithium composite transition metal oxides (hereinafter simply referred to as "NCM-based lithium composite transition metal oxides") have been developed in which part of the cobalt (Co) is replaced with nickel (Ni) and manganese (Mn). However, the NCM-based lithium composite transition metal oxides developed so far are generally in the form of secondary particles formed by agglomeration of primary particles, have a large specific surface area, low particle strength, and a high content of lithium by-products, and therefore have problems such as a large amount of gas generation during cell operation and poor stability. As such, the stability of the NCM-based lithium composite transition metal oxides developed so far has been limited, particularly in terms of their application to high-voltage batteries. In addition, in order to increase the capacity per unit volume of the electrode, it is necessary to increase the rolling density, and the NCM-based lithium composite transition metal oxides developed so far have problems such as increased resistance and gas generation due to severe particle cracking during rolling.

[0007] In particular, in the case of high-nickel (Ni) NCM-based lithium transition metal composite oxides, in which the nickel (Ni) content is increased to ensure high capacity, the structural and chemical stability is further reduced and it is more difficult to ensure thermal stability. Furthermore, such high-nickel NCM-based lithium transition metal composite oxides have a problem of reduced long-term life due to the phenomenon of particle cracking occurring after rolling. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] Korean Patent Publication No. 10-2014-0018685 Summary of the Invention [Problem to be solved by the invention]

[0009] The present invention has been devised to solve the above-mentioned problems of the conventional technology, and aims to provide a positive electrode material containing a high-nickel (High-Ni) lithium composite transition metal oxide in which crack generation and particle breakage are improved.

[0010] Another object of the present invention is to provide a cathode material and a manufacturing method thereof that reduce the surface area exposed after rolling by mitigating the occurrence of cracks and particle breakage in the cathode material, thereby reducing side reactions with the electrolyte, and improving the long-term life. [Means for solving the problem]

[0011] In order to solve the above problems, a positive electrode material, a method for producing the positive electrode material, a positive electrode, and a lithium secondary battery are provided.

[0012] (1) The present invention provides a method for producing a 100% 100% 100% 15 ... 50 The first positive electrode active material includes a lithium composite transition metal oxide represented by the following chemical formula 1, and the first positive electrode active material has an average particle size (D ) at which a maximum peak is shown in the area-accumulated particle size distribution of the first positive electrode active material measured by a laser diffraction particle size measurement device. 50 The present invention provides a cathode material having a secondary particle having a number of primary particles of 6 to 30 as measured by a cross-sectional SEM image of the secondary particle. [Chemical formula 1] Li a Ni x Co y M 1 z M 2 w O2 In the above Chemical Formula 1, M 1 is one or more selected from Mn and Al, 2 is one or more selected from the group consisting of Zr, B, W, Mo, Mg, Ce, Hf, Ta, Nb, La, Ti, Sr, Ba, F, P, Si, and S, and 0.9≦a≦1.1, 0.7≦x<1, 0 <y≦0.2、0<z≦0.2、0≦w≦0.1である。

[0013] (2) The present invention provides, in the above (1), a positive electrode material, in which the lithium composite transition metal oxide represented by the chemical formula 1 is represented by the following chemical formula 1-1: [Chemical formula 1-1] Li a Ni x Co y Mn z M 2 w O2 In the above Chemical Formula 1-1, M 2 is one or more selected from the group consisting of Zr, B, W, Mo, Mg, Ce, Hf, Ta, Nb, La, Ti, Sr, Ba, F, P, Si, and S, and 0.9≦a≦1.1, 0.7≦x<1, 0 <y≦0.2、0<z≦0.2、0≦w≦0.1である。

[0014] (3) The present invention provides a positive electrode material according to (1) or (2) above, wherein the first positive electrode active material includes a coating layer formed on a surface of a lithium composite transition metal oxide and containing one or more elements selected from the group consisting of Al, Ti, W, B, F, P, Mg, Ni, Co, Fe, Cr, V, Cu, Ca, Zn, Zr, Nb, Mo, Sr, Sb, Bi, Si, Ta, and S.

[0015] (4) The present invention provides a positive electrode material according to any one of the above (1) to (3), wherein the second positive electrode active material contains a lithium composite transition metal oxide represented by the following chemical formula 2: [Chemical formula 2] Li a’ Ni x’ Co y’ M 3 z’ M 4w’ O2 In the above Chemical Formula 2, M 3 is one or more selected from Mn and Al, 4 is one or more selected from the group consisting of Zr, B, W, Mo, Mg, Ce, Hf, Ta, Nb, La, Ti, Sr, Ba, F, P, Si, and S, and 0.9≦a'≦1.1, 0.8≦x'<1, 0 <y'<0.2、0<z'<0.2、0≦w'≦0.1である。

[0016] (5) In any one of the above (1) to (4), the present invention further comprises: 50 ) is the average particle size (D 50 ) to provide a smaller cathode material.

[0017] (6) In any one of the above (1) to (5), the first positive electrode active material has an average particle size (D 50 ) is 2 μm or more and 7 μm or less.

[0018] (7) In any one of the above (1) to (6), the second positive electrode active material has an average particle size (D 50 The present invention provides a positive electrode material having a grain size of more than 7 μm and not more than 20 μm.

[0019] (8) The present invention provides a cathode material according to any one of the above (1) to (7), wherein the amount of change in particle size calculated by the following mathematical formula 1 is 6.0 or less: [Formula 1] Grain size change = P0-P1 In Equation 1, P0 is the intensity of the maximum peak shown in an area cumulative particle size distribution graph of the cathode material, and P1 is the intensity of a peak shown in a region corresponding to the particle size of the P0 peak in an area cumulative particle size distribution graph measured after pressing the cathode material at 9 tons.

[0020] (9) The present invention provides a method for producing a first positive electrode active material including a lithium composite transition metal oxide represented by the following chemical formula 1 by mixing a positive electrode active material precursor represented by the following chemical formula 3 and a lithium raw material, and then performing primary firing to form a pre-fired product (S10). The method further includes performing secondary firing on the pre-fired product at a temperature of more than 850° C. and not more than 890° C. to form a first positive electrode active material including a lithium composite transition metal oxide represented by the following chemical formula 1 (S20). 50 and (S30) mixing a second positive electrode active material having a different characteristic. [Chemical formula 1] Li a Ni x Co y M 1 z M 2 w O2 In the above Chemical Formula 1, M 1 is one or more selected from Mn and Al, 2 is one or more selected from the group consisting of Zr, B, W, Mo, Mg, Ce, Hf, Ta, Nb, La, Ti, Sr, Ba, F, P, Si, and S, and 0.9≦a≦1.1, 0.7≦x<1, 0 <y≦0.2、0<z≦0.2、0≦w≦0.1であり、 [Chemical formula 3] [Ni x Co y M 1 z M 2 w ](OH)2 In the above Chemical Formula 3, M 1 is one or more selected from Mn and Al, 2 is one or more selected from the group consisting of Zr, B, W, Mo, Mg, Ce, Hf, Ta, Nb, La, Ti, Sr, Ba, F, P, Si and S, and 0.7≦x<1, 0 <y≦0.2、0≦z≦0.2、0≦w≦0.1である。

[0021] (10) The present invention provides a method for producing a positive electrode material according to the above (9), wherein the positive electrode active material precursor represented by the chemical formula 3 is represented by the following chemical formula 3-1: [Chemical formula 3-1] [Nix Co y Mn z ](OH)2 In the above formula 3-1, 0.7≦x<1, 0 <y≦0.2、0≦z≦0.2である。

[0022] (11) In the present invention, in the above (9) or (10), during the primary firing in the step (S10), M 1 Containing raw materials (M 1 is one or more selected from Mn and Al; 2 Containing raw materials (M 2 is one or more selected from the group consisting of Zr, B, W, Mo, Mg, Ce, Hf, Ta, Nb, La, Ti, Sr, Ba, F, P, Si and S.) or a mixture thereof.

[0023] (12) In any one of the above (9) to (11), the present invention further comprises the step of: 1 Containing raw materials (M 1 is one or more selected from Mn and Al; 2 Containing raw materials (M 2 is one or more selected from the group consisting of Zr, B, W, Mo, Mg, Ce, Hf, Ta, Nb, La, Ti, Sr, Ba, F, P, Si and S.) or a mixture thereof.

[0024] (13) The present invention provides the method for producing a cathode material according to any one of the above (9) to (12), wherein the primary firing in the step (S10) is carried out at a temperature of 600°C or higher and lower than 800°C.

[0025] (14) The present invention provides a method for producing a cathode material according to any one of (9) to (13), further comprising, after the secondary firing in step (S20) and before step (S30), performing at least one of the following steps: a step (S21) of washing the lithium composite transition metal oxide represented by Chemical Formula 1 with water; and a step (S22) of mixing the lithium composite transition metal oxide represented by Chemical Formula 1 with a coating raw material containing one or more elements selected from the group consisting of Al, Ti, W, B, F, P, Mg, Ni, Co, Fe, Cr, V, Cu, Ca, Zn, Zr, Nb, Mo, Sr, Sb, Bi, Si, Ta, and S, followed by heat treatment to form a coating layer.

[0026] (15) The present invention provides the method for producing a cathode material according to (14), wherein in the step (S22), the heat treatment is carried out at a temperature of 200° C. or higher and 700° C. or lower.

[0027] (16) The present invention provides a positive electrode comprising the positive electrode material according to any one of (1) to (8) above.

[0028] (17) The present invention provides a lithium secondary battery comprising the positive electrode according to (16) above, a negative electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte. Effect of the Invention

[0029] The cathode material of the present invention contains a high-nickel (High-Ni) lithium composite transition metal oxide, which allows for high capacity, and reduces the occurrence of cracks and particle breakage, thereby reducing the surface area exposed after rolling and reducing side reactions with the electrolyte, thereby improving the long-term life. [Brief description of the drawings]

[0030] [Figure 1] 1 is a cross-sectional SEM (Scanning Electron Microscope) image of a first positive electrode active material particle prepared in Example 1. [Diagram 2]1 is a cross-sectional SEM (Scanning Electron Microscope) image of a first positive electrode active material particle prepared in Comparative Example 1. [Diagram 3] 1 is a cross-sectional SEM (Scanning Electron Microscope) image of a first positive electrode active material particle prepared in Comparative Example 2. [Figure 4] 1 is a cross-sectional SEM (Scanning Electron Microscope) image of a first positive electrode active material particle prepared in Comparative Example 3. [Diagram 5] 1 is a graph showing particle size distributions of the positive electrode material powders produced in Example 1 and Comparative Example 1 before and after a 9-ton press. [Figure 6] 1 is a graph showing the capacity retention rate and the resistance increase rate at 45° C. of mono-cells including the positive electrode materials produced in Examples 1 and 2 and Comparative Examples 1 to 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0031] The present invention will now be described in further detail in order to facilitate understanding of the present invention.

[0032] The terms and words used in the description of the present invention and the claims should not be interpreted in a limited manner to their ordinary or dictionary meanings, but should be interpreted in a manner that is consistent with the technical idea of ​​the present invention, based on the principle that the inventors can appropriately define the concepts of terms in order to best describe their invention.

[0033] In the present invention, the term "primary particle" refers to the smallest particle unit that can be distinguished as a single mass when a cross section of a positive electrode active material is observed through a scanning electron microscope (SEM), and may be composed of a plurality of crystal grains.

[0034] In the present invention, the term "secondary particle" refers to a secondary structure formed by agglomeration of a plurality of primary particles. The average particle size of the secondary particles can be measured using a particle size analyzer.

[0035] In the present invention, the term "particle size (D n )" means the particle size at the n% point of the area cumulative distribution by particle size. That is, D 50 is the particle size at the 50% point of the cumulative area distribution by particle size, and D 90 is the particle size at the 90% point of the cumulative area distribution by particle size, D 10 is the particle size at the 10% point of the particle size area cumulative distribution. n can be measured using the laser diffraction method. Specifically, the powder to be measured is dispersed in a dispersion medium, then introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac S3500), and the particle size distribution is calculated by measuring the difference in the diffraction pattern due to particle size when the particles pass through a laser beam. The particle diameters at the points of 10%, 50%, and 90% of the area cumulative distribution by particle size in the measuring device are calculated, and the D 10 , D 50 and D. 90 can be measured.

[0036] In the present invention, the term "average particle size (D 50 )" means the particle size at the 50% point, which is the point at which the maximum peak of the area cumulative particle size distribution measured using the laser diffraction particle size measuring device is shown.

[0037] Cathode material The present invention provides a cathode material.

[0038] According to one embodiment of the present invention, the cathode material has an average particle size (D 50 The first positive electrode active material includes a lithium composite transition metal oxide represented by the following Chemical Formula 1, and the first positive electrode active material has an average particle size (D ) at which a maximum peak is shown in the area-accumulated particle size distribution of the first positive electrode active material measured using a laser diffraction particle size measurement device. 50 The number of primary particles measured in a cross-sectional SEM image of the secondary particles having the above structure may be 6 to 30.

[0039] [Chemical formula 1] Li a Ni x Co y M 1 z M 2 w O2

[0040] In the above Chemical Formula 1, M 1 can be one or more selected from Mn and Al, 2 may be one or more selected from the group consisting of Zr, B, W, Mo, Mg, Ce, Hf, Ta, Nb, La, Ti, Sr, Ba, F, P, Si, and S, and 0.9≦a≦1.1, 0.7≦x<1, 0 <y≦0.2、0<z≦0.2、0≦w≦0.1であることができる。

[0041] According to an embodiment of the present invention, the positive electrode material contains the first positive electrode active material, and thus can contain a high-nickel (High-Ni) lithium composite transition metal oxide to ensure high capacity, and can reduce the surface area exposed after rolling by mitigating the generation of cracks and particle breakage, thereby reducing side reactions with the electrolyte and improving the long life.

[0042] According to one embodiment of the present invention, in Formula 1, M 1 can contain Mn or Mn and Al simultaneously.

[0043] According to one embodiment of the present invention, in Formula 1, M 2 can be one or more selected from the group consisting of Zr, B, W, Mo, Mg, Ce, Hf, Ta, Nb, La, Ti, Sr, Ba, F, P, Si, and S, and can contain Zr in order to further improve the structural stability of the lithium composite transition metal oxide.

[0044] According to an embodiment of the present invention, in Formula 1, a represents a molar ratio of lithium in the lithium composite transition metal oxide, and may be 0.9≦a≦1.1, 0.95≦a≦1.08, or 1≦a≦1.08.

[0045] According to an embodiment of the present invention, in Formula 1, x represents a molar ratio of nickel in the lithium composite transition metal oxide, and may be 0.7≦x<1, 0.80≦x≦0.99, 0.80≦x≦0.95, 0.80≦x≦0.90, or 0.80≦x≦0.85. Within this range, the capacity characteristics can be further improved.

[0046] According to an embodiment of the present invention, in the formula 1, y represents a molar ratio of cobalt in the lithium composite transition metal oxide, and is 0 <y≦0.2、0<y≦0.15または0.01≦y≦0.10であることができる。

[0047] According to one embodiment of the present invention, in the formula 1, z is M in the lithium composite transition metal oxide. 1 The molar ratio of 0 <z≦0.2、0<z≦0.15または0.01≦z≦0.15であることができる。

[0048] According to one embodiment of the present invention, in the formula 1, the w is M in the lithium composite transition metal oxide. 2 and may be 0≦w≦0.1, or 0≦w≦0.05.

[0049] According to an embodiment of the present invention, the lithium transition metal composite oxide represented by Formula 1 may be represented by the following Formula 1-1.

[0050] [Chemical formula 1-1] Li a Ni x Co y Mn z M 2 w O2

[0051] In the above Chemical Formula 1-1, M 2may be one or more selected from the group consisting of Zr, B, W, Mo, Mg, Ce, Hf, Ta, Nb, La, Ti, Sr, Ba, F, P, Si, and S, and 0.9≦a≦1.1, 0.7≦x<1, 0 <y≦0.2、0<z≦0.2、0≦w≦0.1であることができ、ここで、M 2 , a, x, y, z and w are as described above in Formula 1.

[0052] According to an embodiment of the present invention, the lithium composite transition metal oxide represented by Formula 1 may be represented by Formula 1-2 below.

[0053] [Chemical formula 1-2] Li a Ni x Co y Mn z1 Al z2 M 2 w O2

[0054] In the above Chemical Formula 1-2, M 2 may be one or more selected from the group consisting of Zr, B, W, Mo, Mg, Ce, Hf, Ta, Nb, La, Ti, Sr, Ba, F, P, Si, and S, and 0.9≦a≦1.1, 0.7≦x<1, 0 <y≦0.2、0<z1≦0.2、0<z2≦0.2、0≦w≦0.1であることができ、ここで、M 2 , a, x, y and w are as described above in Formula 1.

[0055] According to an embodiment of the present invention, in the formula 1-2, z1 represents a molar ratio of manganese in the lithium composite transition metal oxide, and is 0 <z1≦0.2、0<z1≦0.15または0.01≦z1≦0.15であることができる。

[0056] According to an embodiment of the present invention, in the formula 1-2, z2 represents a molar ratio of aluminum in the lithium composite transition metal oxide, and is 0 <z2≦0.2、0<z2≦0.15または0.01≦z2≦0.15であることができる。

[0057] According to an embodiment of the present invention, the first positive electrode active material may include a coating layer formed on the surface of the lithium composite transition metal oxide and containing one or more elements selected from the group consisting of Al, Ti, W, B, F, P, Mg, Ni, Co, Fe, Cr, V, Cu, Ca, Zn, Zr, Nb, Mo, Sr, Sb, Bi, Si, Ta and S. In this case, the contact between the lithium composite transition metal oxide and the electrolyte can be blocked to effectively suppress gas generation and elution of transition metals due to side reactions with the electrolyte, and the surface structure of the lithium composite transition metal oxide can be stabilized to prevent deterioration of the structure of the first positive electrode active material during charging and discharging. As a specific example, the first positive electrode active material may include a coating layer formed on the surface of the lithium composite transition metal oxide and containing one or more elements selected from the group consisting of Al, Co and B. In this case, the life characteristics can be further improved and an increase in resistance can be further suppressed.

[0058] According to an embodiment of the present invention, the first positive electrode active material has an average particle size (D ) at which a maximum peak of an area-accumulated particle size distribution of the first positive electrode active material is shown, as measured by a laser diffraction particle size measuring device. 50 The number of primary particles measured in a cross-sectional SEM image of the secondary particles having the average particle diameter (D) at which the maximum peak of the area-accumulated particle size distribution of the first positive electrode active material is shown may be 6 to 30. 50 The number of primary particles measured in a cross-sectional SEM image of the secondary particles having a diameter of 10 to 20 mm may be 6 or more, 7 or more, 8 or more, 9 or more, 10 or more, or 11 or more, and may be 30 or less, 29 or less, 28 or less, 27 or less, 26 or less, 25 or less, 24 or less, 23 or less, 22 or less, 21 or less, 20 or less, 19 or less, 18 or less, or 17 or less. Within this range, the deterioration of capacity characteristics is prevented, and the occurrence of cracks and breakage of particles is alleviated, thereby reducing the surface area exposed after rolling, reducing side reactions with the electrolyte, and improving the long life.

[0059] According to an embodiment of the present invention, the first positive electrode active material has an average particle size (D ) at which a maximum peak of an area-accumulated particle size distribution of the first positive electrode active material is shown, as measured by a laser diffraction particle size measuring device. 50 ), i.e., the average particle size of secondary particles (D 50 The ratio of the number of primary particles measured in the cross-sectional SEM image to the average particle size (D 50 )" can be 1.0 or more, 1.1 or more, 1.2 or more, 1.3 or more, 1.4 or more, 1.5 or more, 1.6 or more, 1.7 or more, 1.8 or more, 1.9 or more, 2.0 or more, 2.1 or more, 2.2 or more, 2.3 or more, 2.4 or more, or 2.5 or more, and can be 15.0 or less, 14.0 or less, 13.0 or less, 12.0 or less, 11.0 or less, 10.0 or less, 9.0 or less, 8.0 or less, 7.0 or less, 6.0 or less, 5.0 or less, or 4.0 or less. Within this range, the deterioration of the capacity characteristics can be prevented, and the occurrence of cracks and the splitting of particles can be alleviated, thereby reducing the surface area exposed after rolling, reducing side reactions with the electrolyte, and improving the long life.

[0060] According to an embodiment of the present invention, the second positive electrode active material may include a lithium composite transition metal oxide represented by Formula 2 below.

[0061] [Chemical formula 2] Li a’ Ni x’ Co y’ M 3 z’ M 4 w’ O2

[0062] In the above Chemical Formula 2, M 3 can be one or more selected from Mn and Al, 4 can be one or more selected from the group consisting of Zr, B, W, Mo, Mg, Ce, Hf, Ta, Nb, La, Ti, Sr, Ba, F, P, Si, and S, and 0.9≦a′≦1.1, 0.8≦x′<1, 0 <y'<0.2、0<z'<0.2、0≦w'≦0.1であることができる。

[0063] According to one embodiment of the present invention, in Formula 2, M 3 can contain Mn or Mn and Al simultaneously.

[0064] According to one embodiment of the present invention, in Formula 2, M 4 can be one or more selected from the group consisting of Zr, B, W, Mo, Mg, Ce, Hf, Ta, Nb, La, Ti, Sr, Ba, F, P, Si, and S, and can contain Zr in order to further improve the structural stability of the lithium composite transition metal oxide.

[0065] According to an embodiment of the present invention, in Formula 2, a' represents a molar ratio of lithium in the lithium composite transition metal oxide, and may be 0.9≦a'≦1.1, 0.95≦a'≦1.08, or 1≦a'≦1.08.

[0066] According to an embodiment of the present invention, in Formula 2, x' represents a molar ratio of nickel in the lithium composite transition metal oxide, and may be 0.8≦x'<1, 0.80≦x'≦0.99, 0.80≦x'≦0.95, 0.80≦x'≦0.90, or 0.85≦x'≦0.90. Within this range, the capacity characteristics can be further improved.

[0067] According to an embodiment of the present invention, in the formula 2, y′ represents a molar ratio of cobalt in the lithium composite transition metal oxide, and is 0 <y'<0.2、0<y'≦0.15または0.01≦y'≦0.10であることができる。

[0068] According to one embodiment of the present invention, in the formula 2, z' is M in the lithium composite transition metal oxide. 3 The molar ratio of 0 <z'<0.2、0<z'≦0.15または0.01≦z'≦0.15であることができる。

[0069] According to one embodiment of the present invention, in Formula 2, w' is M in the lithium composite transition metal oxide. 4and may be 0≦w′≦0.1, or 0≦w′≦0.05.

[0070] According to an embodiment of the present invention, the lithium transition metal composite oxide represented by Formula 2 may be represented by Formula 2-1 below.

[0071] [Chemical formula 2-1] Li a’ Ni x’ Co y’ Mn z1’ Al z2’ M 4 w’ O2

[0072] In the above Chemical Formula 2-1, M 4 can be one or more selected from the group consisting of Zr, B, W, Mo, Mg, Ce, Hf, Ta, Nb, La, Ti, Sr, Ba, F, P, Si, and S, and 0.9≦a′≦1.1, 0.8≦x′<1, 0 <y'<0.2、0<z1'<0.2、0<z2'<0.2、0≦w'≦0.1であることができ、ここで、M 4 , a', x', y' and w' are as described in Formula 1 above.

[0073] According to an embodiment of the present invention, in the formula 2-1, z1' represents a molar ratio of manganese in the lithium composite transition metal oxide, and is 0 <z1'≦0.2、0<z1'≦0.15または0.01≦z1'≦0.15であることができる。

[0074] According to one embodiment of the present invention, in the formula 2-1, z2' represents a molar ratio of aluminum in the lithium composite transition metal oxide, and is 0 <z2'≦0.2、0<z2'≦0.15または0.01≦z2'≦0.15であることができる。

[0075] According to an embodiment of the present invention, the first positive electrode active material has an average particle size (D 50 ) is the average particle size (D 50In this case, the average particle size (D) at which the maximum peak of the area-accumulated particle size distribution of the first positive electrode active material is shown as measured using a laser diffraction particle size measuring device may be smaller than the average particle size (D 50 The number of primary particles measured from a cross-sectional SEM image of the secondary particles having the first positive electrode active material is 6 to 30, and the grain size is large, and the first positive electrode active material has a monolith-like form as elementary particles, which can reduce the generation of cracks and breakage of particles, reduce the surface area exposed after rolling, and reduce side reactions with the electrolyte, thereby improving the long life.

[0076] According to an embodiment of the present invention, the first positive electrode active material has an average particle size (D 50 ) may be 2 μm or more and 7 μm or less, and for example, 2 μm or more, 2.5 μm or more, 3 μm or more, 3.5 μm or more, or 4 μm or more, and may be 7 μm or less, 6.5 μm or less, 6 μm or less, 5.5 μm or less, 5 μm or less, or 4.5 μm or less. 50 ) may be more than 7 μm and less than 20 μm, and specific examples thereof may be 7.5 μm or more, 8 μm or more, 8.5 μm or more, 9 μm or more, 9.5 μm or more, or 10 μm or more, and may be 20 μm or less, 19 μm or less, 18 μm or less, 17 μm or less, 16 μm or less, 15 μm or less, 14 μm or less, 13 μm or less, 12 μm or less, or 11 μm or less. Within this range, the first positive electrode active material is packed between the second positive electrode active material particles, thereby producing a positive electrode with high packing density, and the second positive electrode active material is included as a large particle size, thereby further improving the capacity characteristics.

[0077] According to one embodiment of the present invention, the cathode material may include the first cathode active material and the second cathode active material in a weight ratio of 1:99 to 50:50, 10:90 to 40:60, or 10:90 to 30:70. Within this range, the first cathode active material can reduce the generation of cracks and particle breakage, reduce the surface area exposed after rolling, and reduce side reactions with the electrolyte, thereby improving the long life, and the second cathode active material can further improve the capacity characteristics.

[0078] As in the present invention, the average particle size (D 50 When a positive electrode active material layer is manufactured using a bimodal positive electrode material including positive electrode active materials having different average particle diameters, a small particle positive electrode active material having a small average particle diameter is filled between particles of a large particle positive electrode active material having a large average particle diameter, thereby manufacturing an electrode with high energy density. However, in the case of a conventional bimodal positive electrode material, cracks occur in the small particle positive electrode active material particles during the rolling process of the positive electrode, which increases the contact area with the electrolyte, thereby increasing the amount of gas generated and deteriorating the life characteristics. In order to improve this, a method of using a single particle positive electrode active material manufactured by increasing the sintering temperature as the small particle positive electrode active material is considered, but in the case of a single particle positive electrode active material, not only is there a limit to achieving high capacity due to poor capacity characteristics, but there is also a problem that the particle strength of the small particle positive electrode active material is excessively high, which may cause cracks to occur in the large particle positive electrode active material during the rolling process. However, the cathode material according to the present invention contains the first cathode active material and the second cathode active material in a bimodal form, and thus can mitigate the generation of cracks and particle breakage from the first cathode active material, reduce the surface area exposed after rolling, and reduce side reactions with the electrolyte, improving the long-term life, while further improving the capacity characteristics from the second cathode active material.

[0079] According to an embodiment of the present invention, the positive electrode material includes the first positive electrode active material and the second positive electrode active material in a bimodal form, and thus a particle size change amount calculated by the following Equation 1 may be 6.0 or less.

[0080] [Formula 1] Grain size change = P0-P1

[0081] In Equation 1, P0 is the intensity of the maximum peak shown in an area cumulative particle size distribution graph of the cathode material, and P1 is the intensity of a peak shown in a region corresponding to the particle size of the P0 peak in an area cumulative particle size distribution graph measured after pressing the cathode material at 9 tons.

[0082] According to an embodiment of the present invention, the positive electrode material may have a particle size change calculated by Equation 1 of 6.0 or less, 5.9 or less, 5.8 or less, 5.7 or less, 5.6 or less, 5.5 or less, 5.4 or less, 5.3 or less, 5.2 or less, 5.1 or less, 5.0 or less, 4.9 or less, 4.8 or less, 4.7 or less, or 4.6 or less, or may be 0 or more, 0.5 or more, 1.0 or more, 1.5 or more, 2.0 or more, 2.5 or more, 3.0 or more, 3.5 or more, or 4.0 or more. Within this range, the generation of cracks and particle breakage due to rolling during the manufacture of the positive electrode can be mitigated.

[0083] Manufacturing method of cathode material The present invention provides a method for producing the cathode material.

[0084] According to an embodiment of the present invention, the method for producing the cathode material includes the steps of: mixing a cathode active material precursor represented by the following formula 3 and a lithium source material, and then primarily firing the mixture to form a pre-fired product (S10); secondary firing the pre-fired product at a temperature of more than 850° C. and not more than 890° C. to form a first cathode active material including a lithium composite transition metal oxide represented by the following formula 1 (S20); and the first cathode active material and the first cathode active material are mixed together to form a first cathode active material having an average particle size (D 50 and mixing (S30) second positive electrode active materials having different properties.

[0085] [Chemical formula 1] Li a Ni x Co y M 1 z M 2w O2

[0086] In Chemical Formula 1, M 1 can be one or more selected from Mn and Al, and M 2 can be one or more selected from the group consisting of Zr, B, W, Mo, Mg, Ce, Hf, Ta, Nb, La, Ti, Sr, Ba, F, P, Si, and S, and 0.9 ≦ a ≦ 1.1, 0.7 ≦ x < 1, 0 < y ≦ 0.2, 0 < z ≦ 0.2, 0 ≦ w ≦ 0.1 can be satisfied. Here, Chemical Formula 1 is as described above.

[0087] [Chemical Formula 3] [Ni x Co y M 1 z M 2 w (OH)2

[0088] In Chemical Formula 3, M 1 can be one or more selected from Mn and Al, and M 2 can be one or more selected from the group consisting of Zr, B, W, Mo, Mg, Ce, Hf, Ta, Nb, La, Ti, Sr, Ba, F, P, Si, and S, and 0.7 ≦ x < 1, 0 < y ≦ 0.2, 0 ≦ z ≦ 0.2, 0 ≦ w ≦ 0.1 can be satisfied.

[0089] According to one embodiment of the present invention, in Chemical Formula 3, M 1 can be Mn, or can contain Mn and Al simultaneously.

[0090] According to one embodiment of the present invention, in Chemical Formula 3, M 2 can be one or more selected from the group consisting of Zr, B, W, Mo, Mg, Ce, Hf, Ta, Nb, La, Ti, Sr, Ba, F, P, Si, and S.

[0091] According to one embodiment of the present invention, in Chemical Formula 3, x represents the molar ratio of nickel in the cathode active material precursor, and 0.7 ≦ x < 1, 0.80 ≦ x ≦ 0.99, 0.80 ≦ x ≦ 0.95, 0.80 ≦ x ≦ 0.90, or 0.80 ≦ x ≦ 0.85, and within this range, the capacity characteristics can be further improved.

[0092] According to one embodiment of the present invention, in Chemical Formula 3, y represents the molar ratio of cobalt in the cathode active material precursor, and 0 < y ≦ 0.2, 0 < y ≦ 0.15, or 0.01 ≦ y ≦ 0.10.

[0093] According to one embodiment of the present invention, in Chemical Formula 3, z represents M in the cathode active material precursor 1 and the molar ratio thereof can be 0 < z ≦ 0.2, 0 < z ≦ 0.15, or 0.01 ≦ z ≦ 0.15.

[0094] According to one embodiment of the present invention, in Chemical Formula 3, w represents M in the cathode active material precursor 2 and the molar ratio thereof can be 0 ≦ w ≦ 0.1 or 0 ≦ w ≦ 0.05.

[0095] According to one embodiment of the present invention, the cathode active material precursor represented by Chemical Formula 3 can be represented by the following Chemical Formula 3-1.

[0096] [Chemical Formula 3-1] [Ni x Co y Mn z (OH)2

[0097] In Chemical Formula 3-1, 0.7 ≦ x < 1, 0 < y ≦ 0.2, and 0 ≦ z ≦ 0.2, and as a specific example, it is as described in Chemical Formula 3 above.

[0098] According to an embodiment of the present invention, the lithium source material may be a lithium-containing sulfate, nitrate, acetate, carbonate, oxalate, citrate, halide, hydroxide, or oxyhydroxide, and specific examples thereof may include Li2CO3, LiNO3, LiNO2, LiOH, LiOH·H2O, LiH, LiF, LiCl, LiBr, LiI, CH3COOLi, Li2O, Li2SO4, Li3C6H5O7, or a mixture thereof.

[0099] According to an embodiment of the present invention, the lithium source material and the positive electrode active material precursor may be mixed so that the molar ratio of Li:total transition metals in the precursor is 1:1 to 1.2:1, or 1:1 to 1.1:1. When the blending ratio satisfies the above range, the crystal structure of the positive electrode active material is well developed, and a positive electrode active material having excellent capacity characteristics and structural stability can be produced.

[0100] According to one embodiment of the present invention, during the primary firing in step (S10), M 1 Containing raw materials (M 1 is one or more selected from Mn and Al; 2 Containing raw materials (M 2 is one or more selected from the group consisting of Zr, B, W, Mo, Mg, Ce, Hf, Ta, Nb, La, Ti, Sr, Ba, F, P, Si and S.) or a mixture thereof can be further mixed.

[0101] According to an embodiment of the present invention, during the secondary firing in step (S20), M 1 Containing raw materials (M 1 is one or more selected from Mn and Al; 2 Containing raw materials (M 2 is one or more selected from the group consisting of Zr, B, W, Mo, Mg, Ce, Hf, Ta, Nb, La, Ti, Sr, Ba, F, P, Si and S.) or a mixture thereof can be further mixed.

[0102] According to one embodiment of the present invention, the M 1The raw materials contained are M 1 It may be an acetate, nitrate, sulfate, halide, sulfide, hydroxide, oxide, or oxyhydroxide containing an element, and specific examples include Mn2O3, MnO2, Mn3O4, MnCO3, Mn(NO3)2, MnSO4, manganese acetate, manganese chloride, manganese hydroxide, Al2O3, Al(OH)3, Al(NO3)3·9H2O, and Al2(SO4)3.

[0103] According to one embodiment of the present invention, the M 2 The raw materials contained are M 2 The salt may be an acetate, nitrate, sulfate, halide, sulfide, hydroxide, oxide, or oxyhydroxide containing the element.

[0104] In the present invention, the M 1 Elements and M 2 The element may be added, as necessary, in a coprecipitation reaction step for producing a positive electrode active material precursor, or may be added when mixed with a lithium source material, or may be added by mixing with a pre-calcined product obtained by primary calcination before secondary calcination. 1 Elements and M 2 When two or more elements are used, each M 1 Elements and M 2 The time points of the elements may be the same or different. 1 In the case where Mn and Al are included as elements, Mn can be added in the coprecipitation step of the precursor, and Al can be added in the step of mixing with the lithium source material, or by mixing with the pre-calcined product after the primary calcination before the secondary calcination.

[0105] According to one embodiment of the present invention, M 1 Elements and M 2The timing of adding the element may be appropriately adjusted in consideration of the final composition of the cathode active material to be prepared. For example, when preparing a cathode active material having a Ni content of more than 80 atm% or 80 mol%, the Al element may be added in a step of mixing with the lithium source material or a step of mixing with the pre-calcined product after the first calcination before the second calcination, rather than during the coprecipitation reaction, and in this case, the adverse effect of Al on the growth of the crystal structure in the coprecipitation step may be prevented.

[0106] According to an embodiment of the present invention, the step (S10) includes mixing a positive electrode active material precursor and a lithium source material, and optionally adding M 1 Ingredients and / or M 2 This may be a step in which the raw materials are mixed and then primarily fired to produce a pre-fired product.

[0107] According to an embodiment of the present invention, the primary firing in step (S10) may be performed to pre-fire a positive electrode active material precursor and a lithium source material to previously remove by-products, such as CO or moisture, generated during firing, to prevent the by-products from adversely affecting the formation of a crystal structure of the positive electrode active material, thereby producing a positive electrode active material of excellent quality.

[0108] According to an embodiment of the present invention, the primary firing in step (S10) may be performed at a temperature lower than the secondary firing described below. For example, the primary firing may be performed at a temperature of 600°C or higher, 610°C or higher, 620°C or higher, 630°C or higher, or 640°C or higher. The primary firing may be performed at a temperature of less than 800°C, 790°C or lower, 780°C or lower, 770°C or lower, 760°C or lower, 750°C or lower, 740°C or lower, 730°C or lower, 720°C or lower, 710°C or lower, or 700°C or lower. Within this range, by-products can be effectively removed, and the transformation of the crystal structure in the primary firing step in which by-products are present can be prevented, thereby enabling the crystal structure to be developed as desired.

[0109] According to an embodiment of the present invention, the step (S20) may be a step of forming a first positive electrode active material including a lithium transition metal composite oxide represented by Chemical Formula 1 by secondary firing the pre-fired product.

[0110] According to an embodiment of the present invention, the secondary firing in step (S20) may be performed at a temperature of more than 850° C., 851° C. or more, 852° C. or more, 853° C. or more, 854° C. or more, 855° C. or more, 860° C. or more, 865° C. or more, 870° C. or more, 875° C. or more, or 880° C. or more, and may be performed at a temperature of 890° C. or less, 885° C. or less, or 880° C. or less. Within this range, the first positive electrode active material including the lithium transition metal composite oxide represented by Chemical Formula 1 formed by the secondary firing may have an average particle size (D ) at which a maximum peak of the area-accumulated particle size distribution of the first positive electrode active material is shown by a laser diffraction particle size measurement device. 50 The number of primary particles measured from a cross-sectional SEM image of the secondary particles having the above structure may be adjusted to 6 to 30.

[0111] According to an embodiment of the present invention, the method for preparing the cathode material may further include a step (S21) of washing the lithium transition metal composite oxide represented by Formula 1 with water after the secondary firing in step (S20) and before performing step (S30).

[0112] According to an embodiment of the present invention, the step (S21) is for removing lithium by-products remaining on the surface of the lithium composite transition metal oxide, and may be performed by a method of washing a positive active material known in the art. As a specific example, the step (S21) may be performed by mixing the lithium composite transition metal oxide with a washing solution, stirring, filtering to remove the washing solution, and then drying. Here, the drying may be performed at a temperature of 50°C to 150°C.

[0113] According to an embodiment of the present invention, the method for preparing the cathode material may further include, if necessary, a step (S22) of forming a coating layer on the surface of the lithium transition metal composite oxide represented by Formula 1 after the secondary firing in step (S20) and before performing step (S30).

[0114] According to an embodiment of the present invention, the (S22) step may be performed by mixing a coating raw material containing the lithium transition metal oxide represented by Chemical Formula 1 with one or more elements selected from the group consisting of Al, Ti, W, B, F, P, Mg, Ni, Co, Fe, Cr, V, Cu, Ca, Zn, Zr, Nb, Mo, Sr, Sb, Bi, Si, Ta, and S, and then heat treating the mixture. The coating raw material may be acetate, nitrate, sulfate, halide, sulfide, hydroxide, oxide, or oxyhydroxide containing the element.

[0115] According to an embodiment of the present invention, the heat treatment in step (S22) may be performed at a temperature of 200° C. to 700° C., 200° C. to 500° C., or 240° C. to 400° C.

[0116] According to one embodiment of the present invention, in the method for producing the cathode material, if necessary, after the secondary firing of the step (S20) and before the step (S30), either the step (S21) or the step (S22) may be performed, or both the step (S21) and the step (S22) may be performed.

[0117] According to an embodiment of the present invention, in the step (S30), the first positive electrode active material and the first positive electrode active material are mixed to have an average particle size (D 50 ) to finally obtain a cathode material, wherein the second cathode active material is as described above.

[0118] According to an embodiment of the present invention, in step (S30), the first and second positive electrode active materials may be mixed in the weight ratio described above according to the purpose of the present invention.

[0119] positive electrode The present invention provides a positive electrode comprising the positive electrode active material.

[0120] According to an embodiment of the present invention, the positive electrode may include a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector, and the positive electrode active material layer may include the positive electrode active material.

[0121] According to an embodiment of the present invention, the positive electrode current collector may include a metal having high conductivity, and may be easily attached to the positive electrode active material layer, and may be non-reactive in the voltage range of the battery. The positive electrode current collector may be, for example, stainless steel, aluminum, nickel, titanium, calcined carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. The positive electrode current collector may have a thickness of typically 3 μm to 500 μm, and may have fine irregularities on the surface of the current collector to enhance the adhesive strength of the positive electrode active material. For example, the positive electrode current collector may be used in various forms, such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0122] According to an embodiment of the present invention, the positive electrode active material layer may selectively include a conductive material and a binder, if necessary, together with the positive electrode material. Here, the positive electrode material may be included in an amount of 80 wt% to 99 wt%, more specifically 85 wt% to 98.5 wt%, based on the total weight of the positive electrode active material layer, and within this range, excellent capacity characteristics may be exhibited.

[0123] According to an embodiment of the present invention, the conductive material is used to give conductivity to the electrode, and can be used without any particular limitation as long as it does not cause a chemical change in the battery constructed and has electronic conductivity. Specific examples include graphite such as natural graphite and artificial graphite; carbon-based materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metal powder or metal fiber such as copper, nickel, aluminum, and silver; conductive tubes such as carbon nanotubes; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive polymers such as polyphenylene derivatives, and among these, one type alone or a mixture of two or more types can be used. The conductive material can be included in an amount of 0.1% by weight to 15% by weight based on the total weight of the positive electrode active material layer.

[0124] According to an embodiment of the present invention, the binder serves to improve adhesion between the positive electrode particles and the adhesive strength between the positive electrode and the current collector.Specific examples of the binder include polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, polymethyl methacrylate, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated-EPDM, styrene butadiene rubber (SBR), fluororubber, polyacrylic acid, and polymers in which hydrogen is substituted with Li, Na, or Ca, or various copolymers thereof, and one or more of these may be used alone or in combination. The binder may be included in an amount of 0.1 wt % to 15 wt % based on the total weight of the positive electrode active material layer.

[0125] According to one embodiment of the present invention, the positive electrode may be manufactured by a conventional method for manufacturing a positive electrode, except for using the positive electrode material. Specifically, the positive electrode may be manufactured by applying a composition for forming a positive electrode active material layer, which is prepared by dissolving or dispersing the positive electrode material and, if necessary, a binder, a conductive material, and a dispersant in a solvent, onto a positive electrode current collector, followed by drying and rolling, or by casting the composition for forming a positive electrode active material layer onto another support, followed by peeling the composition from the support, and laminating the resulting film onto a positive electrode current collector.

[0126] According to an embodiment of the present invention, the solvent may be a solvent commonly used in the art, and may include dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), dimethylformamide (DMF), acetone, water, etc., and one or more of these may be used alone or in combination. The amount of the solvent used is sufficient to dissolve or disperse the cathode material, conductive material, binder, and dispersant in consideration of the coating thickness of the slurry and the manufacturing yield, and to have a viscosity that can show excellent thickness uniformity when applied to manufacture a cathode.

[0127] Lithium secondary battery The present invention provides a lithium secondary battery including the positive electrode.

[0128] According to an embodiment of the present invention, the lithium secondary battery may include the positive electrode, the negative electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte. The lithium secondary battery may further include a battery container that houses an electrode assembly of the positive electrode, the negative electrode, and the separator, and a sealing member that seals the battery container.

[0129] According to an embodiment of the present invention, the negative electrode may include a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector.

[0130] According to an embodiment of the present invention, the negative electrode current collector is not particularly limited as long as it does not cause a chemical change in the battery and has high conductivity, and may be, for example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface treated with carbon, nickel, titanium, silver, or aluminum-cadmium alloy. The negative electrode current collector may have a thickness of typically 3 μm to 500 μm, and may have fine irregularities formed on the surface of the current collector, as with the positive electrode current collector, to strengthen the binding force of the negative electrode active material. For example, the negative electrode current collector may be used in various forms, such as a film, sheet, foil, net, porous body, foam, or nonwoven fabric.

[0131] According to an embodiment of the present invention, the negative electrode active material layer may optionally include a binder and a conductive material in addition to the negative electrode active material.

[0132] According to an embodiment of the present invention, the negative electrode active material may be a compound capable of reversible intercalation and deintercalation of lithium. Specific examples include carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; metallic compounds capable of alloying with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, and Al alloys; metallic oxides capable of doping and dedoping lithium such as SiOβ(0<β<2), SnO2, vanadium oxide, and lithium vanadium oxide; and composites including the metallic compounds and carbonaceous materials such as Si-C composites and Sn-C composites. Any one or a mixture of two or more of these may be used. In addition, a metallic lithium thin film may be used as the negative electrode active material. In addition, the carbon material may be either low crystalline carbon or high crystalline carbon. Representative examples of low crystalline carbon include soft carbon and hard carbon, and representative examples of high crystalline carbon include amorphous, plate-like, flaky, spherical or fibrous natural graphite or artificial graphite, kish graphite, pyrolytic carbon, mesophase pitch based carbon fiber, meso-carbon microbeads, mesophase pitches, and high-temperature fired carbon such as petroleum or coal tar pitch derived cokes. The negative electrode active material may be included in an amount of 80 wt% to 99 wt% based on the total weight of the negative electrode active material layer.

[0133] According to an embodiment of the present invention, the binder of the negative electrode active material layer is a component that helps to bind between the conductive material, the active material, and the current collector, and is usually added in an amount of 0.1% by weight to 10% by weight based on the total weight of the negative electrode active material layer. Examples of such binders include polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated-EPDM, styrene-butadiene rubber, nitrile-butadiene rubber, fluororubber, and various copolymers thereof.

[0134] According to an embodiment of the present invention, the conductive material of the negative electrode active material layer is a component for further improving the conductivity of the negative electrode active material, and may be added in an amount of 10% by weight or less, preferably 5% by weight or less, based on the total weight of the negative electrode active material layer. Such a conductive material is not particularly limited as long as it does not cause a chemical change in the battery and has conductivity, and examples of the conductive material include graphite such as natural graphite and artificial graphite; carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers such as carbon fibers and metal fibers; carbon fluoride; metal powders such as aluminum and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives.

[0135] According to an embodiment of the present invention, the negative electrode may be manufactured by coating a composition for forming a negative electrode active material layer, which is prepared by dissolving or dispersing a negative electrode active material, and optionally a binder and a conductive material, in a solvent, on a negative electrode current collector and drying the composition. Alternatively, the negative electrode active material layer may be manufactured by casting the composition for forming a negative electrode active material layer on a separate support, peeling it off from the support, and laminating the resulting film on the negative electrode current collector.

[0136] According to an embodiment of the present invention, the separator separates the negative electrode and the positive electrode and provides a path for lithium ions to move. Any separator that is generally used in lithium secondary batteries may be used without any particular limitation. In particular, a separator that has low resistance to ion movement of the electrolyte and has excellent electrolyte humidification ability is preferred. Specifically, a porous polymer film, for example, a porous polymer film made of a polyolefin-based polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminate structure of two or more layers thereof may be used. In addition, a conventional porous nonwoven fabric, for example, a nonwoven fabric made of high-melting point glass fiber, polyethylene terephthalate fiber, etc. may be used. In addition, a coated separator containing a ceramic component or a polymeric material may be used to ensure heat resistance or mechanical strength, and may be selectively used in a single layer or multilayer structure.

[0137] According to an embodiment of the present invention, the electrolyte may be, but is not limited to, an organic liquid electrolyte, an inorganic liquid electrolyte, a solid polymer electrolyte, a gel-type polymer electrolyte, a solid inorganic electrolyte, a molten inorganic electrolyte, etc. that can be used in manufacturing a lithium secondary battery. As a specific example, the electrolyte may include an organic solvent and a lithium salt.

[0138] According to an embodiment of the present invention, the organic solvent may be any solvent that can act as a medium through which ions involved in the electrochemical reaction of the battery can move. Specifically, the organic solvent may be an ester solvent such as methyl acetate, ethyl acetate, γ-butyrolactone, or ε-caprolactone; an ether solvent such as dibutyl ether or tetrahydrofuran; a ketone solvent such as cyclohexanone; an aromatic hydrocarbon solvent such as benzene or fluorobenzene; dimethylcarbonate (DMC), diethylcarbonate (DEC), methylethylcarbonate (MEC), ethylmethylcarbonate (EMC), ethylene carbonate (EC), or propylene carbonate (propylene carbonate). Examples of the solvents that can be used include carbonate-based solvents such as polycarbonate (PC) and polycarbonate-based solvents such as ethyl alcohol and isopropyl alcohol; nitriles such as R-CN (R is a straight-chain, branched or cyclic hydrocarbon group having 2 to 20 carbon atoms, which may contain a double bond aromatic ring or an ether bond); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolane; and sulfolanes. Among these, carbonate-based solvents are preferred, and a mixture of a cyclic carbonate (e.g., ethylene carbonate or propylene carbonate) having high ionic conductivity and high dielectric constant that can enhance the charge / discharge performance of a battery and a low-viscosity straight-chain carbonate compound (e.g., ethyl methyl carbonate, dimethyl carbonate or diethyl carbonate) is more preferred.

[0139] According to one embodiment of the present invention, the lithium salt can be used without any particular limitation as long as it is a compound that can provide lithium ions used in a lithium secondary battery. Specifically, the anion of the lithium salt can be F - , Cl - , Br - , I - , NO3 - , N(CN)2 - , BF4 - , CF3CF2SO3 - , (CF3SO2)2N - , (FSO2)2N - , CF3CF2(CF3)2CO - , (CF3SO2)2CH - , (SF5)3C - , (CF3SO2)3C - , CF3(CF2)7SO3 - , CF3CO2 - , CH3CO2 - , SCN - and (CF3CF2SO2)2N - The lithium salt may be at least one selected from the group consisting of LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI, or LiB(C2O4)2. The lithium salt is preferably used in a concentration range of 0.1M to 2.0M. When the lithium salt concentration is within the above range, the electrolyte has appropriate conductivity and viscosity, so that it can exhibit excellent electrolyte performance and lithium ions can move effectively.

[0140] According to an embodiment of the present invention, the electrolyte may further contain one or more additives such as haloalkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethyl alcohol amine, cyclic ethers, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethyl alcohol, or aluminum trichloride, for the purpose of improving the life characteristics of the battery, suppressing the decrease in the capacity of the battery, improving the discharge capacity of the battery, etc. Here, the additives may be contained in an amount of 0.1% by weight to 5% by weight based on the total weight of the electrolyte.

[0141] The lithium secondary battery including the positive electrode active material according to the present invention stably exhibits excellent capacity characteristics, output characteristics and life characteristics, and is therefore useful in portable devices such as mobile phones, notebook computers and digital cameras, and in the field of electric vehicles such as hybrid electric vehicles (HEVs) and electric vehicles (EVs).

[0142] The external shape of the lithium secondary battery of the present invention is not particularly limited, and may be a cylindrical shape using a can, a square shape, a pouch shape, a coin shape, or the like.

[0143] The lithium secondary battery according to the present invention can be used as a battery cell used as a power source for a small device, and can also be preferably used as a unit battery in a medium- to large-sized battery module including a large number of battery cells.

[0144] According to an embodiment of the present invention, there is provided a battery module including the lithium secondary battery as a unit cell, and a battery pack including the same.

[0145] According to an embodiment of the present invention, the battery module or the battery pack may be used as a power source for one or more medium- to large-sized devices, such as a power tool; an electric vehicle (EV), a hybrid electric vehicle, and an electric vehicle (PHEV), including a plug-in hybrid electric vehicle; or a power storage system.

[0146] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention may be embodied in various different forms and should not be construed as limited to the embodiments set forth herein.

[0147] Working Example Example 1 <Production of first positive electrode active material> Lithium source material LiOH·H20 and positive electrode active material precursor Ni 0.83 Co 0.05 Mn 0.12 (OH)2(D 50 =4.6μm) was mixed so that the molar ratio of Li: transition metals in the precursor (Ni+Co+Mn) was 1.06:1, and ZrO2 was further mixed, and then calcined at 640℃ for 5 hours to produce a pre-calcined product. ZrO2 was mixed so that Zr was 1,000ppm relative to the total weight of the pre-calcined product. Next, the pre-calcined product was secondarily calcined at 880℃ for 6 hours to produce a lithium composite transition metal oxide containing Zr, LiNi 0.83 Co 0.05 Mn 0.12 Manufactured the O2.

[0148] The lithium composite transition metal oxide thus prepared was mixed with 100 g of water and stirred for 5 minutes, washed with water, and separated and filtered using a filter press so that the water content of the washed product was 5% to 10%, and then dried at 130° C. The washed and dried lithium composite transition metal oxide was then mixed with H3BO3 in a weight ratio of 100:0.286 and heat-treated at 300° C. for 4 hours to prepare a cathode active material coated with a B solid solution.

[0149] <Production of cathode materials> The positive electrode active material and the average particle size (D 50 ) is 10μm LiNi 0.86 Co 0.05 Mn 0.07 Al 0.02 The positive electrode material was prepared by mixing O2 and O2 in a weight ratio of 2:8.

[0150] Example 2 <Production of first positive electrode active material> Lithium source material LiOH·H20 and positive electrode active material precursor Ni 0.83 Co 0.05 Mn 0.12 (OH)2(D 50 =4.6μm) was mixed so that the molar ratio of Li: transition metals in the precursor (Ni+Co+Mn) was 1.06:1, ZrO2 was further mixed, and the mixture was fired at 640℃ for 5 hours to produce a pre-fired product. ZrO2 was mixed so that Zr was 1,000ppm relative to the total weight of the pre-fired product. Next, Al(OH)3 was further mixed into the pre-fired product so that Al was 600ppm relative to the weight of the pre-fired product, and the product was secondarily fired at 880℃ for 6 hours to produce a lithium composite transition metal oxide containing Zr and Al, LiNi 0.83 Co 0.05 Mn 0.12 Manufactured the O2.

[0151] The lithium composite transition metal oxide thus prepared was mixed with 100 g of water and stirred for 5 minutes, washed with water, and separated and filtered using a filter press so that the water content of the washed product was 5% to 10%, and then dried at 130° C. The washed and dried lithium composite transition metal oxide was then mixed with H3BO3 in a weight ratio of 100:0.286 and heat-treated at 300° C. for 4 hours to prepare a cathode active material coated with a B solid solution.

[0152] <Production of cathode materials> The positive electrode active material and the average particle size (D 50 ) is 10μm LiNi 0.86 Co 0.05 Mn0.07 Al 0.02 The positive electrode material was prepared by mixing the positive electrode active materials of O2 and ZnO in a weight ratio of 2:8.

[0153] Comparative Example 1 A cathode material was prepared in the same manner as in Example 1, except that the secondary firing was performed at 800°C.

[0154] Comparative Example 2 A cathode material was prepared in the same manner as in Example 1, except that the secondary firing was performed at 840°C.

[0155] Comparative Example 3 A cathode material was prepared in the same manner as in Example 1, except that the secondary firing was performed at 900°C.

[0156] Experimental Example Experimental Example 1: Measurement of the average particle size of the first positive electrode active material and taking a cross-sectional SEM image 0.5 g of the first positive electrode active material powder prepared in Examples 1 and 2 and Comparative Examples 1 to 3 was dispersed in water containing a small amount of sodium hexametaphosphate ((NaPO3)6), and the average particle size (D 50 The results are shown in Table 1. The average particle size (D 50 ) means the average particle size of the secondary particles.

[0157] In addition, 10 g of positive electrode active material particles were collected from the first positive electrode active material powder produced in Examples 1 and 2 and Comparative Examples 1 to 3, and a cross section was cut using an ion milling system (Hitachi Corporation, IM4000), and the measured average particle size (D 50 The cross-sectional SEM images of the secondary particles having the cross-sectional area of ​​each positive electrode active material were obtained. The cross-sectional SEM images obtained were analyzed to count the number of primary particles in the cross section of each positive electrode active material, and the average value was calculated. The results are shown in Table 1.

[0158] A cross-sectional SEM image of a sample taken from the positive electrode active material powder of Example 1 is shown in FIG. 1, a cross-sectional SEM image of a sample taken from the positive electrode active material powder of Comparative Example 1 is shown in FIG. 2, a cross-sectional SEM image of a sample taken from the positive electrode active material powder of Comparative Example 2 is shown in FIG. 3, and a cross-sectional SEM image of a sample taken from the positive electrode active material powder of Comparative Example 3 is shown in FIG. 4.

[0159] [Table 1]

[0160] As shown in Table 1 and FIGS. 1 to 4, the first positive electrode active materials prepared in Examples 1 and 2 according to the present invention had an average particle size (D 50 In the cross-sectional SEM images of the secondary particles having the above-mentioned structure, the number of primary particles is within the range defined by the present invention, whereas in the cases of Comparative Examples 1 and 2, the number of primary particles exceeds the upper limit of 30, and in the case of Comparative Example 3, the number of primary particles does not reach the lower limit of 6.

[0161] Experimental example 2: Measurement of particle size change of positive electrode material 0.5 g of the cathode material powder produced in Examples 1 and 2 and Comparative Examples 1 to 3 was dispersed in water containing a small amount of sodium hexametaphosphate ((NaPO3)6), and the areal cumulative particle size distribution of the cathode material was measured using a laser diffraction particle size measurement device (Microtrac S-3500).

[0162] Next, 2 g of the cathode material powder was collected and pressed at a pressure of 9 tons. The pressed cathode material powder was then dispersed in water to which a small amount of sodium hexametaphosphate ((NaPO3)6) had been added. The areal cumulative particle size distribution of the cathode material after the 9-ton press was measured using a laser diffraction particle size measurement device (Microtrac S-3500).

[0163] Using the results of the particle size distribution measurements before and after pressing, the amount of change in particle size was calculated according to the following formula 1. The results are shown in Table 2.

[0164] [Formula 1] Grain size change = P0-P1

[0165] In Equation 1, P0 is the intensity of the maximum peak shown in an area cumulative particle size distribution graph of the cathode material, and P1 is the intensity of a peak shown in a region corresponding to the particle size of the P0 peak in an area cumulative particle size distribution graph measured after pressing the cathode material at 9 tons.

[0166] FIG. 5 is a graph showing the areal cumulative particle size distribution of the positive electrode material powders of Example 1 and Comparative Example 1 before and after pressing.

[0167] [Table 2]

[0168] 5, it was confirmed that the cathode materials including the first cathode active materials prepared in Examples 1 and 2 according to the present invention exhibited a small amount of particle size change, while the cathode materials including the first cathode active materials prepared in Comparative Examples 1 and 2 exhibited a large amount of particle size change.

[0169] Experimental example 3: Evaluation of high temperature life The cathode materials prepared in Examples 1 and 2 and Comparative Examples 1 to 3, Denka black as a conductive material, and PVDF as a binder were mixed in a weight ratio of 97.5:1.15:1.35 in N-methyl-2-pyrrolidone (NMP) solvent to prepare a cathode slurry. The cathode slurry was applied onto an aluminum current collector, dried, and then rolled to prepare a cathode.

[0170] Next, natural graphite and artificial graphite as negative electrode active materials, carbon black as conductive material, and SBR and CMC as binders were mixed in water in a weight ratio of 95:1.5:3.5 to prepare a negative electrode slurry. The negative electrode slurry was applied onto a copper current collector, dried, and then rolled to prepare a negative electrode.

[0171] An electrode assembly was prepared by interposing a separator between the positive and negative electrodes, and then the electrode assembly was placed inside a battery case, and an electrolyte was injected to prepare a mono cell. The electrolyte was prepared by dissolving 0.7M LiPF6 and 0.3M LiFSI in an organic solvent in which ethylene carbonate: ethyl methyl carbonate: diethyl carbonate were mixed in a volume ratio of 3:3:4, and 100 μl of the electrolyte was injected per electrode. The prepared mono cell was subjected to formation and initial gas was removed to prepare a mono cell for evaluating high temperature life.

[0172] The prepared monocell was charged at a constant current of 0.33 C and discharged at a constant current of 0.33 C at 25° C. to measure the initial capacity and resistance. Next, in a chamber at 45° C., charging at a constant current of 0.33 C and discharging at a constant current of 0.33 C constituted one cycle, and continuous charging and discharging were performed, and every 100 cycles, charging at a constant current of 0.33 C and discharging at a constant current of 0.33 C in a chamber at 25° C. were performed to measure the capacity retention rate and resistance increase rate relative to the initial capacity and resistance, and the results are shown in Table 3 below.

[0173] FIG. 6 is a graph showing the capacity retention rate and the resistance increase rate for mono-cells including the positive electrode materials of Examples 1 and 2 and Comparative Examples 1 to 3.

[0174] [Table 3]

[0175] As shown in Table 3 and FIG. 6, the mono cells including the cathode materials prepared in Examples 1 and 2 according to the present invention showed little decrease in capacity retention rate and mitigated increase in resistance with increasing number of cycles. This is because the average particle size (D 50 In the cross-sectional SEM image of the secondary particles having the above structure, the number of primary particles is adjusted within the range limited by the present invention, so that the amount of change in particle size of the cathode material is small. This reduces the occurrence of cracks and particle breakage, thereby reducing the surface area exposed after rolling and reducing side reactions with the electrolyte.

[0176] On the other hand, the average particle size of secondary particles (D 50 In the cross-sectional SEM images of the secondary particles having an average particle diameter (D 50 In the cross-sectional SEM image of the secondary particles having a number of primary particles, which is less than 6, the lower limit of the range limited by the present invention, it was confirmed that the monocell including the cathode material including the first cathode active material manufactured in Comparative Example 3 showed a larger decrease in capacity retention with increasing number of cycles than in the Examples, and the resistance increase rate also increased sharply. In the cases of Comparative Examples 1 and 2, particle cracks occurred in the first cathode active material particles, increasing the contact area with the electrolyte, and in the case of Comparative Example 3, it is expected that the capacity characteristics themselves were inferior and, instead, cracks were caused in the second cathode active material, resulting in a decrease in life characteristics.

[0177] From these results, it was confirmed that the cathode material of the present invention contains a high-nickel (High-Ni) lithium transition metal composite oxide, which can ensure high capacity, and reduces the occurrence of cracks and particle breakage, thereby reducing the surface area exposed after rolling, reducing side reactions with the electrolyte, and improving the long-term life.

Claims

1. Average particle size (D 50 a positive electrode material having a bimodal particle size distribution including a first positive electrode active material and a second positive electrode active material having different particle sizes; The first positive electrode active material includes a lithium composite transition metal oxide represented by the following Chemical Formula 1: The first positive electrode active material has an average particle size (D) at which a maximum peak of the area-accumulated particle size distribution of the first positive electrode active material is shown, as measured using a laser diffraction particle size measurement device. 50 The number of primary particles measured in a cross-sectional SEM image of the secondary particles having the above structure is 6 to 30, A cathode material, wherein the first cathode active material has an average particle size (D 50 ) smaller than an average particle size (D 50 ) of the second cathode active material. [Chemical formula 1] Li a Ni x Co y M 1 z M 2 w O 2 In the above Chemical Formula 1, M 1 is one or more selected from Mn and Al, M 2 is one or more selected from the group consisting of Zr, B, W, Mo, Mg, Ce, Hf, Ta, Nb, La, Ti, Sr, Ba, F, P, Si and S, 0.9≦a≦1.1, 0.7≦x<1, 0<y≦0.2, 0<z≦0.2, and 0≦w≦0.

1.

2. The positive electrode material according to claim 1, wherein the lithium composite transition metal oxide represented by the chemical formula 1 is represented by the following chemical formula 1-1. [Chemical formula 1-1] Li a Ni x Co y Mn z M 2 w O 2 In the above Chemical Formula 1-1, M 2 is one or more selected from the group consisting of Zr, B, W, Mo, Mg, Ce, Hf, Ta, Nb, La, Ti, Sr, Ba, F, P, Si and S, 0.9≦a≦1.1, 0.7≦x<1, 0<y≦0.2, 0<z≦0.2, and 0≦w≦0.

1.

3. 2. The cathode material according to claim 1, wherein the first cathode active material comprises a coating layer formed on a surface of a lithium composite transition metal oxide and containing one or more elements selected from the group consisting of Al, Ti, W, B, F, P, Mg, Ni, Co, Fe, Cr, V, Cu, Ca, Zn, Zr, Nb, Mo, Sr, Sb, Bi, Si, Ta, and S.

4. The positive electrode material according to claim 1 , wherein the second positive electrode active material comprises a lithium composite transition metal oxide represented by the following chemical formula 2: [Chemical formula 2] Li a’ Ni x’ Co y’ M 3 z’ M 4 w’ O 2 In the above Chemical Formula 2, M 3 is one or more selected from Mn and Al, M 4 is one or more selected from the group consisting of Zr, B, W, Mo, Mg, Ce, Hf, Ta, Nb, La, Ti, Sr, Ba, F, P, Si and S, 0.9≦a'≦1.1, 0.8≦x'<1, 0<y'<0.2, 0<z'<0.2, and 0≦w'≦0.

1.

5. The first positive electrode active material has an average particle size (D 50 2. The cathode material according to claim 1, wherein the average particle diameter is 2 μm or more and 7 μm or less.

6. The second positive electrode active material has an average particle size (D 50 2. The cathode material according to claim 1, wherein the average particle diameter is greater than 7 μm and less than or equal to 20 μm.

7. The cathode material according to claim 1 , wherein the amount of change in particle size calculated by the following Equation 1 is 6.0 or less. [Formula 1] Particle size change amount = P 0 -P 1 In the above formula 1, P 0 is the intensity of the maximum peak shown in the area cumulative particle size distribution graph of the positive electrode material, P 1 is a graph showing the area cumulative particle size distribution of the positive electrode material measured after pressing the positive electrode material with 9 tons. 0 It is the intensity of the peak shown in the region corresponding to the particle size of the peak.

8. A step (S10) of mixing a positive electrode active material precursor represented by the following chemical formula 3 and a lithium raw material, and then performing primary firing to form a pre-fired product; A step (S20) of secondary firing the pre-fired product at a temperature of more than 850° C. and not more than 890° C. to form a first positive electrode active material including a lithium composite transition metal oxide represented by the following Chemical Formula 1: The first positive electrode active material and the second positive electrode active material have an average particle size (D 50 (S30) mixing second positive electrode active materials having different The method for producing a cathode material, wherein an average particle size (D 50 ) of the first cathode active material is smaller than an average particle size (D 50 ) of the second cathode active material. [Chemical formula 1] Li a Ni x Co y M 1 z M 2 w O 2 In the above Chemical Formula 1, M 1 is one or more selected from Mn and Al, M 2 is one or more selected from the group consisting of Zr, B, W, Mo, Mg, Ce, Hf, Ta, Nb, La, Ti, Sr, Ba, F, P, Si and S, 0.9≦a≦1.1, 0.7≦x<1, 0<y≦0.2, 0<z≦0.2, and 0≦w≦0.1, [Chemical formula 3] [Ni x Co y M 1 z M 2 w ](O+) 2 In the above Chemical Formula 3, M 1 is one or more selected from Mn and Al, M 2 is one or more selected from the group consisting of Zr, B, W, Mo, Mg, Ce, Hf, Ta, Nb, La, Ti, Sr, Ba, F, P, Si and S, 0.7≦x<1, 0<y≦0.2, 0≦z≦0.2, and 0≦w≦0.

1.

9. The method for producing a positive electrode material according to claim 8, wherein the positive electrode active material precursor represented by the chemical formula 3 is represented by the following chemical formula 3-1. [Chemical formula 3-1] [Ni x Co y Mn z ](OH) 2 In the above chemical formula 3-1, 0.7≦x<1, 0<y≦0.2, and 0≦z≦0.

2.

10. During the primary firing in step (S10), M 1 Containing raw materials (M 1 is one or more selected from Mn and Al. 2 Containing raw materials (M 2 is one or more selected from the group consisting of Zr, B, W, Mo, Mg, Ce, Hf, Ta, Nb, La, Ti, Sr, Ba, F, P, Si and S. The method for producing a positive electrode material according to claim 8, further comprising mixing the above-mentioned elements or a mixture thereof.

11. During the secondary firing in step (S20), M 1 Containing raw materials (M 1 is one or more selected from Mn and Al. 2 Containing raw materials (M 2 is one or more selected from the group consisting of Zr, B, W, Mo, Mg, Ce, Hf, Ta, Nb, La, Ti, Sr, Ba, F, P, Si and S. The method for producing a positive electrode material according to claim 8, further comprising mixing the above-mentioned elements or a mixture thereof.

12. The method for producing a cathode material according to claim 8, wherein the primary firing in the step (S10) is performed at a temperature of 600°C or higher and lower than 800°C.

13. After the secondary firing in step (S20) and before performing step (S30), A step (S21) of washing the lithium composite transition metal oxide represented by the chemical formula 1 with water; 9. The method for producing a cathode material according to claim 8, further comprising the step of: mixing the lithium transition metal oxide represented by Chemical Formula 1 with a coating raw material containing one or more elements selected from the group consisting of Al, Ti, W, B, F, P, Mg, Ni, Co, Fe, Cr, V, Cu, Ca, Zn, Zr, Nb, Mo, Sr, Sb, Bi, Si, Ta, and S, and then performing a heat treatment to form a coating layer (S22).

14. The method for producing a cathode material according to claim 13, wherein in the step (S22), the heat treatment is performed at a temperature of 200° C. or more and 700° C. or less.

15. A positive electrode comprising the positive electrode material of any one of claims 1 to 7.

16. A lithium secondary battery comprising: the positive electrode according to claim 15; a negative electrode; a separator interposed between the positive electrode and the negative electrode; and an electrolyte.

Citation Information

Patent Citations

  • Lithium complex oxide

    JP2021070626A

  • Cathode Active Material for Secondary Battery and Lithium Secondary Battery Comprising the Same

    KR1020140018685A

  • Positive electrode active substance for non-aqueous electrolyte secondary cell, and non-aqueous electrolyte secondary cell

    WO2020003642A1

  • Cathode optimized for improving high-temperature lifespan characteristics, and secondary battery comprising same

    WO2021125535A1